Peran Balai Besar Rehabilitasi Sosial Bina Daksa Prof. Dr. Soeharso Surakarta dalam Upaya Pemenuhan Hak Bagi Penyandang Disabilitas Fisik pada Proses Rehabilitasi - Saputro, Muhammad Bayu; , Mutimatun Ni'ami, S.H., M.Hum (2017)
This research aims to know the role of Balai Besar Rehabilitasi Sosial Bina Daksa Prof. Dr. Soeharso Surakarta in the effort of physically disabled right fulfillment at rehabilitation process and occurred problems in physically disabled right fulfillment process in Balai Besar Rehabilitasi Sosial Bina Daksa Prof. Dr. Soeharso Surakarta. The method of approach that the writer used is empirical law research. Kind of research that the writer used is sosiological research with descriptive characteristic. The location of the research at Balai Besar Rehabilitasi Sosial Bina Daksa Prof. Dr. Soeharso Surakarta. Writer uses primary data sources and secondary data sources. The method of data collection that the writer used are literature, observation and interview. Based on the result of the research and discussions, it can be concluded that Balai Besar Rehabilitasi Sosial Bina Daksa Prof. Dr. Soeharso Surakarta has several services in term physically disabled right fulfillment such as rehabilitation service: medical, psychological sosial, education and vocational. Keywords: right fulfillment, physically disabled, rehabilitation